Midterm results of uterine artery embolization using narrow-size calibrated embozene microspheres - Stampfl, Ulrike; Radeleff, Boris; Sommer, Christof-Matthias; Stampfl, Sibylle; Dahlke, Angelika; Bellemann, Nadine; Kauczor, Hans-Ulrich; Richter, Götz Martin (CardioVascular and interventional radiology, 2011)
Purpose: To evaluate safety and efficacy of uterine artery embolization using narrow-size-range polyphosphazene-coated hydrogel microspheres (Embozene, CeloNova Biosciences, Newnan, GA). Methods: Between May 2006 and September 2008, a total of 121 consecutive patients (mean ± SD age 42.1 ± 5.4 years, range 30.5–51.5 years) were enrolled onto this single-center study. The primary study endpoint was safety as assessed by the society of interventional radiology (SIR) classification. The secondary endpoint was efficacy, which was based on a 1-year magnetic resonance imaging study and relief of symptoms documented by the Medical Outcomes Study 36-Item Short-Form Health Survey questionnaire over a 2-year interval. Results: The mean ± SD diameter of the dominant fibroid was 6.4 ± 2.6 (range, 2.9–13.9) cm and the mean volume 137.2 ± 245.1 (range, 5.3–1184) ml. Most patients had multiple fibroids with 11% more than 10. A total of 240 of 242 interventions were completed as planned, a technical success rate of 99.2%. According to the SIR classification, one type A, eight type C, and one type D complication occurred. Total devascularization was noted in 96% (116 of 121) of dominant fibroids. Volume decrease was 4% at 2 weeks, 52% (P < 0.001) at 3 months, 78% (P < 0.001) at 6 months, and 91% at 12 months (P < 0.001). The latter difference was statistically significant (P = 0.007). A total of 92% had improved hypermenorrhea at 1 year and 94% at 2 years. Dysmenorrhea was improved in 96% at 1 year and in 95% at 2 years. The overall health status score was 60.4 ± 26.2 points at baseline and 96.9 ± 3.8 after 1 year (P = 0.0019). Conclusion: Uterine artery embolization with Embozene microspheres is a safe procedure. Its efficacy is demonstrated by high fibroid devascularization and volume reduction rates and significant improvements of clinical symptoms and quality-of-life scores during follow-up.